Revolutionising Energy Generation for Agriculture Utilization in Malaysia: Photovoltaic Greenhouse Concept - Choong P.Y.; Chua Y.L.; Ker P.J. (Penerbit Akademia Baru, 2024)
Malaysia is a fortunate country graced by abundant sunlight, potentially having success in the application of photovoltaic (PV) powered greenhouses to safeguard food security. This research seeks to develop a design basis for PV greenhouse suitable for application in Malaysia. The motivation behind this research arises from the fact that while there have been studies on the application of PV greenhouses globally, most of them have focused on Europe, the Mediterranean, and Japan. The research will include two experimental prototypes and one control prototype, all featuring identical mono-span roof PV greenhouses with a 15 tilt angle and E-W orientation which has been determined based on literature review. For stage 1 of the research, the prototypes will differ in terms of the PV array arrangements on the roof